Beyond Therapy: A Conceptual Review of Emotion-Focused Coaching for Mental Well-Being - Kovbuz, Valeriya (European Scientific Journal, ESJ, 2025)
Emotion-Focused Coaching (EFC) is used as a non-therapeutic coaching approach that bases its work on emotions to help people develop personally and achieve life satisfaction. This literature review integrates theoretical foundations with academic research to study EFC’s effects on emotional awareness and self-compassion development and its impact on psychological resilience and relationship quality. EFC serves people who maintain normal functioning in their personal and professional lives through a structured method to identify and validate emotions before they need clinical help. The research findings demonstrate that EFC has four main advantages, which include better emotional regulation and identification, reduced self-criticism and enhanced self-acceptance, improved stress management, and strengthened interpersonal connection skills. The literature suggests that EFC may be particularly suitable in education, healthcare, and leadership contexts with high emotional demands, complementing goal-oriented coaching models. Research on Emotional-Focused Coaching currently exists as conceptual studies, which prove the necessity for emotional facilitation training, but more empirical studies are needed to measure EFC effectiveness and evaluate its cross-cultural adaptability.